Pengelolaan Layanan Perpustakaan - Rochmah, Erma Awalien (Taallum: Jurnal Pendidikan Islam, 2016)
Library essentially, is an information manager which has been packaged in the various forms of media. The library service management must be on the need oriented and the user satisfaction. It is based on the kinds of library, the objective of library establishment and the principles of library services by utilizing the development and advancement of information technology. There are three systems of services that can be implemented in a library that is open services system, the system covered services and system services mix. The implementation of the service depends on the circumstances of each library.